Incidence of pressure injury in an adult intensive care unit (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Objective: To identify the incidence of pressure injury (PI) in adults hospitalized in an intensive care, as well as the risk factors and characteristics of their development. Method: Descriptive, prospective and observational research. Between June and September 2016, with a sample (n=58) eligible patients, demographic and clinical data were collected, the Braden scale score and intrinsic and extrinsic risk factors, besides having performed the daily observation of the entire surface of the skin regarding the development of PI. From the tabulated data, descriptive statistical analysis was performed. Results: The sample was predominantly men (55.1%), hospitalized for neurological conditions (32.8%) and with a very high risk of PI at admission (94.8%). The incidence of PI was 20.6%, and the sacral region was the most aff ected by these injuries (76.5%). Conclusion: The incidence of PI was 20.6%, in a clientele with a high risk for the development of this adverse event, which mainly aff ected the sacral region.
Keywords: Pressure injury; Intensive care units; Patient safety; Nursing care; Stomatherapy